Impact of Laparoscopic Lens Contamination in Operating Theaters: A Study on the Frequency and Duration of Lens Contamination and Commonly Utilized Techniques to Maintain Clear Vision. Issue 4 (August 2016) - Yong, Nathanael; Grange, Philippe; Eldred-Evans, David
Abstract : Introduction: In laparoscopy, contamination of the distal lens is problematic. Not only a cause of frustration, repeatedly cleaning the laparoscope takes up significant time and disrupts the operative flow. Our study aims to explore and describe quantitatively this particular issue within the operating theaters of a major teaching hospital. Materials and Methods: We recorded data assessing the occurrence of impaired vision on the screen display and quantified the occurrence, duration, and modality of cleaning events. Data were recorded on a time-line sheet and collected for basic quantitative analysis as reported below. A brief interview with the surgeons was carried out at the end of each procedure. Results: A total of 64 hours of laparoscopy covering 25 procedures in 4 surgical disciplines were observed. The study found that 56% of the operation was performed with a clear display, while 37% of the time was spent impaired vision. Seven percent of the operation was spent cleaning the distal lens. The interviews recorded a unison sense of frustration and safety concerns regarding lens contamination. Conclusions: Our observational study demonstrates that one third of the duration of a laparoscopic procedure is performed without perfectly clear display. The suboptimal display during an operation is similar to that of driving with a dirty windshield and having to step out of the car to clean it before continuing with the journey. The disruption to operative flow is transcribed as frustration felt by surgeons when display is compromised and having to clean the lens. However, the economical impact of cleaning the lens during the operation remains to be demonstrated.